2008
DOI: 10.1037/1931-3896.2.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Does music induce emotion? A theoretical and methodological analysis.

Abstract: Is music ubiquitous in part because it is causally linked to emotion? In this article, a comprehensive theoretical and methodological reevaluation is presented of a classical problem: The direct induction of emotion by music (M3 E). The author's Prototypical Emotion-Episode Model (PEEM) is used in the conceptual critique. A close scrutiny of the major published studies, and the author's new data regarding some substantive and methodological issues in several of these, reveal weak support for the M3 E model. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(165 citation statements)
references
References 99 publications
(233 reference statements)
5
155
0
5
Order By: Relevance
“…As was mentioned earlier, listening to music can put us in a certain mood or emotional state (see [21,86], cf. [87]), either positive or negative.…”
Section: Emotional Mediation Of Music's Influence On Tastementioning
confidence: 99%
“…As was mentioned earlier, listening to music can put us in a certain mood or emotional state (see [21,86], cf. [87]), either positive or negative.…”
Section: Emotional Mediation Of Music's Influence On Tastementioning
confidence: 99%
“…Of these, aesthetic chills have been the most widely studied. It's hard to find a label for such a motley band of experiences: they don't have much in common except that they aren't simple preferences or discrete emotions ( Konečni, 2005, Konečni, 2008, they seem to be common responses to music ( Grewe, Kopiez, & Altenmüller, 2009), and they are often part of powerful aesthetic experiences ( Gabrielsson, 2006;Strange & Taylor, 2008).…”
Section: The Three Strands Of Aesthetics Researchmentioning
confidence: 99%
“…Support for this distinction comes from the observation that music seems to have no implications either for survival or for goal pursuit (Kivy, 1990). This makes it unlikely that music may trigger 'everyday emotions', such as fear, sadness, happiness, and anger, whose elicitation is typically understood in terms of adaptive response (Konečni, 2008;Scherer, 2004). Indeed it has been shown that music can induce more complex emotions than those evoked by everyday life events, and that, contrary to affective responses induced by everyday life events, affective responses to music are characterised by a more fine grained range of positive emotions than negative ones (Zentner, Grandjean, & Scherer, 2008).…”
Section: Contemporary Evidence and Debatementioning
confidence: 99%